Village health worker training for complications of labor and delivery in rural Maharashtra, India - Peterson, Wynn (Dove Medical Press, 2014)
BACKGROUND: By analyzing the perspectives of village health worker/trainers with the Comprehensive Rural Health Project (CRHP), this study aimed to investigate their level of knowledge of treatment, risks, and prevention of complications of labor and delivery and to evaluate current teaching methods. METHODS: Three focus groups of six village health workers/trainers were conducted and divided according to level of experience. The resulting semistructured discussion was analyzed according to grounded theory. RESULTS: Participants displayed strong content retention with respect to clinically relevant knowledge. Village health workers experienced barriers, including lack of education and casteism, which affected their ability to establish trust in the community. Clinical observation was perceived to be the most effective learning method and is recommended for teaching village health workers about the treatment and prevention of the complications of labor and delivery. CONCLUSION: When implementing this training model in comparable global communities, local culture and its impact on establishing trust is an important factor to consider.